Direction of illumination controls gametophyte orientation in seedless plants and related algae - Cardona-Correa, Christopher (Plant Signal Behav, 2015)
The environmental influences that determine dorsiventral or axial gametophyte orientation are unknown for most modern seedless plants. To fill this gap, an experimental laboratory system was employed to evaluate the relative effects of light direction and gravity on body orientation of the dorsiventral green alga Coleochaete orbicularis, and gametophytes of liverworts Blasia pusilla and Marchantia polymorpha, early-diverging moss Sphagnum compactum, and fern Ceratopteris richardii, the latter functioning as experimental control. Replicate clonal cultures were experimentally illuminated only from above, only from below, or from multiple directions, with the same near-saturation PAR level for periods brief enough to minimize nutrient limitation effects, and orientation of new growth was evaluated. For all species tested, direction of illumination exerted stronger control over gametophyte body orientation than gravity. When illuminated only from below: 1) axial Sphagnum gametophores that had initially grown into an overlying air space inverted growth by 180°, burrowing into the substrate; 2) new growth of dorsiventral Blasia, Marchantia, and Ceratopteris gametophytes–whose ventral rhizoids initially penetrated agar substrate and dorsal surfaces initially faced overlying airspace–twisted 180° so that ventral surfaces bearing rhizoids faced overlying air space and rhizoids extended into the air; and 3) Coleochaete lost typical dorsiventral organization and diagnostic dorsal hairs. Direction of illumination also exerted stronger control over orientation of liverwort new growth than surface contact did. These results indicate that early land plants likely inherited light-directed gametophyte body orientation from ancestral streptophyte algae and suggest a mechanism for reorientation of gametophyte-dominant land plants after spatial disturbance.